2022
DOI: 10.21511/bbs.17(2).2022.14
|View full text |Cite
|
Sign up to set email alerts
|

A cross-impact analysis of the bank payment card market parameters and non-financial sectors’ indicators in the Ukrainian economy

Abstract: In Ukraine, card payment systems develop at a rate similar to that of modern digital payment instruments in most European countries. The purpose of the paper is to establish interdependence and explain the nature of changing situations in the market of bank payment cards (BPC) taking into account the dynamics of economic development parameters in non-financial sectors of the Ukrainian economy. The methodology of the study includes graphic methods analyzing the dynamics of economic development indicators and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Research conducted by BCG has revealed that transitioning to a cashless model could boost a country's annual GDP by up to 3 percentage points. Conversely, cash-based economies tend to miss out on significant opportunities in the global commercialization landscape and may experience slower economic growth (Massi et al, 2019). However, it is important to note that the impact of adopting cashless payment methods on economic growth is a phenomenon that becomes significantly observable in the long run.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by BCG has revealed that transitioning to a cashless model could boost a country's annual GDP by up to 3 percentage points. Conversely, cash-based economies tend to miss out on significant opportunities in the global commercialization landscape and may experience slower economic growth (Massi et al, 2019). However, it is important to note that the impact of adopting cashless payment methods on economic growth is a phenomenon that becomes significantly observable in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in interest rates can affect borrowing costs, spending patterns, and saving behavior, all of which impact the adoption and usage of digital payment platforms. A favorable interest rate environment could encourage consumers and businesses to option for digital payments, while high-interest rates might promote cash usage as a means of evading transaction costs (Massi et al, 2019;Simon Oyewole et al, 2013).…”
Section: Introductionmentioning
confidence: 99%